2004
DOI: 10.1073/pnas.0403100101
|View full text |Cite
|
Sign up to set email alerts
|

Commitment of C3H10T1/2 pluripotent stem cells to the adipocyte lineage

Abstract: The increase of adipose tissue mass associated with obesity is due in part to an increase in the number of adipocytes. This hyperplasia results from recruitment of pluripotent stem cells present in the vascular stroma of adipose tissue. A model cell culture system has been developed that recapitulates this process both ex vivo and in vivo. After treatment of pluripotent C3H10T1͞2 stem cells with bone morphogenic protein 4 (BMP4) during proliferation followed by differentiation inducers at growth arrest, the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
331
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(358 citation statements)
references
References 25 publications
18
331
0
2
Order By: Relevance
“…Several studies have demonstrated that BMP4 has a well‐established role in triggering commitment of mesenchymal stem cells into the osteogenic and adipogenic lineage 8, 9, 10, 15. In addition, BMP4‐regulated osteogenic and adipogenic lineage commitment of MSCs is mutually exclusive 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that BMP4 has a well‐established role in triggering commitment of mesenchymal stem cells into the osteogenic and adipogenic lineage 8, 9, 10, 15. In addition, BMP4‐regulated osteogenic and adipogenic lineage commitment of MSCs is mutually exclusive 8.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous studies that knockdown of Lox disrupts the BMP4‐induced adipocyte lineage commitment from MSCs10 and a theoretical inverse relationship exists between osteogenic and adipogenic lineage commitment and differentiation of MSCs,6 we hypothesized that knockdown of Lox would enhance BMP4‐induced osteogenesis of MSCs. To explore this, C3H10T1/2 cells, a well‐characterized mesenchymal stem cells20 and faithful model of MSCs to study adipocytic and osteogenic commitment and differentiation both in vitro and in vivo,8, 9, 21 was used. As expected, two key osteogenic transcription factors, Runx2 and Osterix, were up‐regulated by BMP4, which were further enhanced by Lox knockdown at the committed stage (day 0) (Figure 1A‐C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 However, this postconfluence mitosis has not been observed in mouse C3H10T1/2 or human preadipocytes. 8,27 It has been suggested that preadipocytes isolated from fat have already undergone the prerequisite clonal expansion in vivo, and thus further cell cycle events would not be observed in such cells. 4 Nevertheless, it is clear that some of the checkpoint proteins for mitosis are involved in regulation of adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro differentiation of C3H10T1/2 cells can be divided into two phases: a commitment phase induced by BMP4 or BMP7 and a differentiation phase induced by a defined cocktail. BMP7 during the commitment phase drives C3H10T1/2 cells to develop into brown adipocytes [8], whereas BMP4 promotes adipogenesis [9]. We treated C3H10T1/2 cells with ATM throughout the BMP4-induced commitment phase and the differentiation phase (group b), or in the commitment phase only (group c), or in the differentiation phase only (group d; Supplementary information, Figure S1D (Cyto C) were upregulated by ATM in a dose-dependent manner ( Figure 1C).…”
Section: Dear Editormentioning
confidence: 99%